PENGARUH PENYALAHGUAAN NARKOBA TERHADAP PERTUMBUHAN EKONOMI MASYARAKAT KELURAHAN BARINGIN - Alimah Nias; Masdelilah; Mawaddah Khofifah; Zainal Efendi Hasibuan (Adpertens: Jurnal Ekonomi dan Manajemen, 2026)
Drug abuse is a social problem that has far-reaching impacts, including on economic growth at the village level. This journal discusses the effect of drug abuse on economic growth in Baringin Village. The research method used is descriptive analysis and case study. The results show that drug abuse has a negative impact on community productivity, unemployment, and decreased village income. In addition, the increase in drug abuse cases also resulted in increased costs for health services and law enforcement, which further burdened the village budget and hindered infrastructure development and community welfare programs. This phenomenon not only affects the individuals involved, but also creates a negative stigma towards the village, which can reduce investment and new job opportunities. Therefore, collaborative efforts between the government, communities and non-governmental organizations are needed to effectively and sustainably address this issue